ÓPTICA INTEGRADA: ELABORACIÓN Y CARACTERIZACIÓN DE GUÍAS DE ONDA PLANAS - Mosquera, Luis (1999)
Coautores: Enver Fernández, JorgeLeón, Hernán Soldevilla, Guido Castillo, Aníbal valera,*Mauro Lomer Ver PDF